Utilization of Technology in Public Policy Making: Opportunities and Challenges - Isnaeni Yuliani; Endang Larasati; Kismartini Kismartini; Tri Yuniningsih (CCIT (Creative Communication and Innovative Technology) Journal, 2024)
Public policy-making is a complex process that requires accurate and timely information to generate effective decisions. In the digital era, information technology has become a crucial tool in supporting this process. This article explores various technologies that can be utilized to optimize public policy-making, as well as the challenges associated with their utilization. Through this analysis, the article offers insights into how more effective strategies in implementing technology can enhance the efficiency and effectiveness of the public policy-making process. This article is the result of a literature review using a conceptual-traditional approach. Primary data in the literature review consists of journals related to the topic under study and some reports sourced from social media. The findings of this study indicate that technology utilization can play a key role in optimizing public policy-making. However, challenges such as limited access and capacity, privacy, and security issues, as well as technological access inequality need to be addressed to ensure that the benefits of technology can serve as powerful tools for creating better and more responsive public policies.